Capital Market Inclusion Improvement Strategies in Central Kalimantan - Riru Apriandami Ngindra; Meitiana Meitiana; Fitria Husnatarina (Pusat Riset dan Inovasi Nasional, 2024)
The capital market plays a crucial role in driving national economic development, including in the Central Kalimantan Province. However, the level of inclusion in this region remains relatively low, with only 5.19% of the productive-age population registered as investors. This study aims to identify the primary obstacles and propose strategic solutions to enhance capital market literacy and participation in Central Kalimantan. The research employs a library research method, focusing on the analysis of scholarly literature, secondary data, and official publications from relevant financial institutions. Through this approach, the study identifies three major barriers to inclusion: (1) the limited availability of Investment Galleries, particularly in educational institutions; (2) inadequate financial education access in remote and rural areas; and (3) a shortage of certified professionals within securities companies. To address these challenges, three strategic initiatives are proposed: (a) expanding the establishment of Investment Galleries in universities and schools without existing capital market partnerships; (b) implementing consistent financial literacy programs through both offline and online platforms, especially targeting remote regions; and (c) offering initial investment incentives to attract and engage new investors. These strategies are expected to improve financial awareness, broaden public participation, and support sustainable growth in capital market activities across Central Kalimantan, ultimately contributing to greater regional economic inclusion.